A high temperature resistant, breakdown resistant, flame retardant and reinforced PA material and preparation method thereof

By adding glass fiber, halogen-free flame retardant and modified zinc oxide to PA66 material, the problem of insufficient flame retardant and aging resistance of PA66 material is solved, and efficient flame retardant and aging resistance is achieved, which significantly improves the performance of high-efficiency flame retardant and aging resistance. Comprehensive properties of materials.

CN117801518BActive Publication Date: 2024-12-20DONGGUAN JINGBAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311857949.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2024-12-20
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The flame retardancy of existing PA66 materials is relatively average, and some flame retardants have weak aging resistance and are easily degraded by factors such as ultraviolet rays, heat, and oxygen, which affects the overall performance of the material.

Method used

Using PA66, glass fiber, halogen-free flame retardant (a mixture of red phosphorus and FR-1), modified zinc oxide and anti-aging agent, it is melt-extruded and granulated in a screw extruder after mixing evenly. Dry to prepare PA materials with good flame retardant, aging resistance and high temperature resistance. Modified zinc oxide is coated with aluminum nitride powder to improve flame retardant properties and enhance material stability through silane coupling agent and heat treatment.

Benefits of technology

It significantly improves the flame retardant performance, aging resistance and high temperature resistance of PA materials, extends the service life of the material, reduces the risks of aging and discoloration, and enhances the comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004859624090000091
    Figure GDA0004859624090000091
Patent Text Reader

Abstract

The present invention relates to the technical field of ABS materials, and specifically discloses a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material and a preparation method thereof, wherein the PA material comprises, by weight: 50-60 parts of PA66, 25-35 parts of glass fiber, 10-18 parts of halogen-free flame retardant, 0.5-2 parts of modified zinc oxide, 0.1-0.5 parts of anti-aging agent, and 0.5-3 parts of lubricant. The PA material prepared by the present invention has good comprehensive performance, and has good strength, flame retardancy, aging resistance, breakdown resistance and high temperature resistance. The present invention further adds modified zinc oxide on the basis of adding halogen-free flame retardant. The zinc oxide in the modified zinc oxide can be used as an effective synergist in combination with red phosphorus and halogen-free flame retardant FR-1, significantly improving the flame retardant performance of the PA material, and the modified zinc oxide in the present invention can effectively improve the strength, breakdown resistance and aging resistance of the PA material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PA materials, and in particular to a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material and a preparation method thereof. Background Art

[0002] PA (polyamide), also known as nylon, is a common polymer material. Common PA materials include PA6 and PA66. PA material has excellent mechanical properties, with high strength and hardness. Its tensile strength and elastic modulus are relatively high, it can withstand large tensile forces, and has excellent fatigue resistance. Therefore, PA materials are widely used in the manufacture of high-strength, fatigue-resistant parts, such as vehicle parts, sports equipment, tools, etc. PA66 has good heat resistance, crystallinity, strength and other properties, but the flame retardancy of PA66 is average. The existing method of adding flame retardants to PA66 to improve its flame retardancy, but some flame retardants have relatively weak aging resistance and are easily affected by ultraviolet rays, heat, oxygen and other factors, causing degradation and aging. It will also bring other negative effects such as aging resistance to PA materials, affecting the comprehensive performance of PA materials. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] The present invention provides a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, which comprises the following raw materials in parts by weight:

[0006] PA66 50-60 parts, glass fiber 25-35 parts, halogen-free flame retardant 10-18 parts, modified zinc oxide 0.5-2 parts, anti-aging agent 0.1-0.5 parts, lubricant 0.5-3 parts;

[0007] Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1;

[0008] PA66 is NPD-002 produced by INVISTA of the United States, and the glass fiber is produced by Jiangsu Jinji Composite Materials Co., Ltd. with the brand name T635C.

[0009] As a further technical solution of the present invention, the following raw materials are included by weight:

[0010] PA66 52 parts, glass fiber 28 parts, halogen-free flame retardant 12 parts, anti-aging agent 0.3 parts, modified zinc oxide 1.5 parts, lubricant 1.5 parts.

[0011] As a further technical solution of the present invention, the preparation method of the modified zinc oxide comprises the following steps:

[0012] Add zinc oxide powder to the solvent, stir at a speed of 300-500 r / min for 10-40 min, stir evenly, and prepare a zinc oxide solution with a concentration of 3-10 wt%, wherein the particle size of the zinc oxide powder is 1-5 microns, and the solvent is one of ethanol and toluene;

[0013] Aluminum nitride powder is added to zinc oxide solution, and stirred at a speed of 450-650r / min for 10-40min, wherein the mass ratio of aluminum nitride powder to zinc oxide powder is 1:2-8, and the particle size of aluminum nitride powder is 20-50 nanometers. Then, a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 60-80°C, and stirring is continued for 20-40min, so that the aluminum nitride powder is evenly coated on the surface of zinc oxide, and the addition amount of the silane coupling agent is 0.5-2% of the mass of the mixed slurry. Finally, the slurry is filtered, dried and solidified, and after removing the solvent, the coated mixture is heat-treated. The heat treatment conditions are: carried out in an inert atmosphere, the heat treatment temperature is 300-600°C, and the time is 30-50min, so as to obtain modified zinc oxide.

[0014] As a further technical solution of the present invention, the silane coupling agent is one of KH550, KH560 and KH570.

[0015] As a further technical solution of the present invention, the mass ratio between the red phosphorus in the halogen-free flame retardant and the halogen-free flame retardant FR-1 is 1:1.5-2.

[0016] As a further technical solution of the present invention, the anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1 to 1.5.

[0017] As a further technical solution of the present invention, the lubricant is molybdenum disulfide.

[0018] Another object of the embodiment of the present invention is to provide a method for preparing a high temperature resistant, breakdown resistant, flame retardant, reinforced PA material, comprising the following steps:

[0019] Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly;

[0020] The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 220-260°C.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a high temperature resistant, breakdown resistant and flame retardant reinforced PA material. The PA material prepared by the invention has good comprehensive performance, and has good strength, flame retardancy, aging resistance, breakdown resistance and high temperature resistance. In the invention, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1, wherein red phosphorus is an effective flame retardant that can release phosphoric acid and promote the carbonization of a polymer, thereby playing a flame retardant role; the halogen-free flame retardant FR-1 is a halogen-free flame retardant, has good heat resistance and stability, and can effectively improve the flame retardancy of the polymer; the invention further adds modified zinc oxide on the basis of adding the halogen-free flame retardant, and the zinc oxide in the modified zinc oxide can be used as an effective synergist in combination with red phosphorus and the halogen-free flame retardant FR-1, and the zinc oxide can generate metal oxides and water vapor during the combustion process, which plays a role in consuming oxygen and reducing the temperature, thereby improving the flame retardancy of the polymer, so that the flame retardancy of the material can be significantly improved by the coordinated use of the halogen-free flame retardant and the modified zinc oxide. The modified zinc oxide in the present invention is obtained by uniformly coating the surface of zinc oxide with aluminum nitride powder. The aluminum nitride itself also has a flame retardant effect, which can further improve the flame retardancy of the PA material. At the same time, aluminum nitride also has high strength and chemical stability. It forms a protective film on the surface of zinc oxide, which can effectively delay the oxidation and phase change of zinc oxide in a high temperature environment, thereby improving the stability and strength of the zinc oxide.

[0023] In addition, the zinc oxide in the modified zinc oxide is a semiconductor material with excellent electrical properties and stability. It can absorb and dissipate static charges, effectively preventing the accumulation of static charges, thereby avoiding breakdown and arc discharge caused by excessive static charges, and can enhance the product's breakdown resistance.

[0024] The present invention also adds an anti-aging agent consisting of antioxidant 1010 and UV-1, wherein antioxidant 1010 can decompose the free radicals generated by PA66 at high temperature, thereby delaying or preventing the oxidation reaction, protecting the PA66 material from oxidation, and extending its service life, and UV-1 can absorb ultraviolet rays, reduce the irradiation of ultraviolet rays on the PA66 material, thereby reducing the oxidation reaction and degradation process caused by ultraviolet rays. In this way, the aging and discoloration of the material can be delayed, and its weather resistance and long-term stability can be improved. In addition, the red phosphorus in the halogen-free flame retardant of the present invention has good aging resistance, and at the same time, red phosphorus can also absorb ultraviolet light, slow down the oxidation reaction, and inhibit the generation of free radicals, thereby delaying the aging process of the material. DETAILED DESCRIPTION

[0025] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention provides a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, which comprises the following raw materials in parts by weight:

[0027] PA66 50-60 parts, glass fiber 25-35 parts, halogen-free flame retardant 10-18 parts, modified zinc oxide 0.5-2 parts, anti-aging agent 0.1-0.5 parts, lubricant 0.5-3 parts;

[0028] Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1.

[0029] The present invention includes the following raw materials by weight:

[0030] PA66 52 parts, glass fiber 28 parts, halogen-free flame retardant 12 parts, anti-aging agent 0.3 parts, modified zinc oxide 1.5 parts, lubricant 1.5 parts.

[0031] In this embodiment, the preparation method of the modified zinc oxide comprises the following steps:

[0032] Add zinc oxide powder to a solvent, stir at a speed of 300-500 r / min for 10-40 min, stir evenly, and prepare a zinc oxide solution with a concentration of 3-10 wt%, wherein the solvent is one of ethanol and toluene;

[0033] Aluminum nitride powder is added to a zinc oxide solution, and stirred at a speed of 450-650r / min for 10-40min, wherein the mass ratio of the aluminum nitride powder to the zinc oxide powder is 1:2-8, and then a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 60-80°C, and stirring is continued for 20-40min, so that the aluminum nitride powder is evenly coated on the surface of the zinc oxide, and the amount of the silane coupling agent added is 0.5-2% of the mass of the mixed slurry. Finally, the slurry is filtered, dried and cured, and after removing the solvent, the coated mixture is heat-treated. The heat treatment conditions are: carried out in an inert atmosphere (such as argon or nitrogen), the heat treatment temperature is 300-600°C, and the time is 30-50min, so as to obtain modified zinc oxide.

[0034] In this embodiment, the silane coupling agent is one of KH550, KH560 and KH570.

[0035] In this embodiment, the mass ratio of the red phosphorus in the halogen-free flame retardant to the halogen-free flame retardant FR-1 is 1:1.5-2.

[0036] In this embodiment, the anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1 to 1.5.

[0037] In this embodiment, the lubricant is molybdenum disulfide.

[0038] Another object of the embodiment of the present invention is to provide a method for preparing a high temperature resistant, breakdown resistant, flame retardant, reinforced PA material, comprising the following steps:

[0039] Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly;

[0040] The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 220-260°C.

[0041] In the embodiment of the present invention, PA66 is NPD-002 produced by INVISTA of the United States, the glass fiber is produced by Jiangsu Jinji Composite Materials Co., Ltd., and its brand is T635C, the particle size of zinc oxide powder is 1-5 microns, and the particle size of aluminum nitride powder is 20-50 nanometers.

[0042] Example 1.

[0043] The present invention provides a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, which comprises the following raw materials in parts by weight:

[0044] PA66 50 parts, glass fiber 32 parts, halogen-free flame retardant 16 parts, modified zinc oxide 1.5 parts, anti-aging agent 0.5 parts, lubricant 2.5 parts;

[0045] Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1.

[0046] In this embodiment, the preparation method of the modified zinc oxide comprises the following steps:

[0047] Add zinc oxide powder to the solvent, stir at a speed of 400 r / min for 30 minutes, stir evenly, and prepare a zinc oxide solution with a concentration of 8 wt%, wherein the solvent is toluene:

[0048] Aluminum nitride powder is added to a zinc oxide solution and stirred at a speed of 500 r / min for 30 minutes, wherein the mass ratio of the aluminum nitride powder to the zinc oxide powder is 1:6, and then a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 80°C, and stirring is continued for 30 minutes, so that the aluminum nitride powder is evenly coated on the surface of the zinc oxide, and the amount of the silane coupling agent added is 2% of the mass of the mixed slurry. Finally, the slurry is filtered, dried and solidified, and after removing the solvent, the coated mixture is heat-treated. The heat treatment conditions are: carried out in an inert atmosphere (argon gas), the heat treatment temperature is 500°C, and the time is 40 minutes, so as to obtain modified zinc oxide.

[0049] In this embodiment, the silane coupling agent is KH570.

[0050] In this embodiment, the mass ratio of the red phosphorus in the halogen-free flame retardant to the halogen-free flame retardant FR-1 is 1:1.8.

[0051] In this embodiment, the anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1.3.

[0052] In this embodiment, the lubricant is molybdenum disulfide.

[0053] Another object of the embodiment of the present invention is to provide a method for preparing a high temperature resistant, breakdown resistant, flame retardant, reinforced PA material, comprising the following steps:

[0054] Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly;

[0055] The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 260°C.

[0056] Example 2.

[0057] The present invention provides a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, which comprises the following raw materials in parts by weight:

[0058] PA66 52 parts, glass fiber 30 parts, halogen-free flame retardant 15 parts, modified zinc oxide 1.5 parts, anti-aging agent 0.5 parts, lubricant 0.5 parts;

[0059] Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1.

[0060] In this embodiment, the preparation method of the modified zinc oxide comprises the following steps:

[0061] The zinc oxide powder was added to the solvent, and stirred at a speed of 400 r / min for 20 min. The mixture was stirred evenly to prepare a zinc oxide solution with a concentration of 6 wt %, wherein the solvent was ethanol:

[0062] Aluminum nitride powder is added to a zinc oxide solution and stirred at a speed of 500 r / min for 20 minutes, wherein the mass ratio of the aluminum nitride powder to the zinc oxide powder is 1:5, and then a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 70°C, and stirring is continued for 30 minutes, so that the aluminum nitride powder is evenly coated on the surface of the zinc oxide, and the amount of the silane coupling agent added is 1% of the mass of the mixed slurry. Finally, the slurry is filtered, dried and solidified, and after removing the solvent, the coated mixture is heat-treated. The heat treatment conditions are: carried out in an inert atmosphere (argon gas), the heat treatment temperature is 500°C, and the time is 40 minutes, so as to obtain modified zinc oxide.

[0063] In this embodiment, the silane coupling agent is KH560.

[0064] In this embodiment, the mass ratio of the red phosphorus in the halogen-free flame retardant to the halogen-free flame retardant FR-1 is 1:1.8.

[0065] In this embodiment, the anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1.4.

[0066] In this embodiment, the lubricant is molybdenum disulfide.

[0067] Another object of the embodiment of the present invention is to provide a method for preparing a high temperature resistant, breakdown resistant, flame retardant, reinforced PA material, comprising the following steps:

[0068] Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly;

[0069] The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 260°C.

[0070] Example 3.

[0071] The present invention provides a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, which comprises the following raw materials in parts by weight:

[0072] PA66 52 parts, glass fiber 28 parts, halogen-free flame retardant 12 parts, anti-aging agent 0.3 parts, modified zinc oxide 1.5 parts, lubricant 1.5 parts;

[0073] Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1.

[0074] The present invention includes the following raw materials by weight:

[0075] In this embodiment, the preparation method of the modified zinc oxide comprises the following steps:

[0076] Add zinc oxide powder to the solvent, stir at a speed of 400 r / min for 20 minutes, stir evenly, and prepare a zinc oxide solution with a concentration of 5wt%, wherein the solvent is ethanol:

[0077] Aluminum nitride powder is added to a zinc oxide solution and stirred at a speed of 600 r / min for 30 minutes, wherein the mass ratio of the aluminum nitride powder to the zinc oxide powder is 1:5, and then a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 70°C, and stirring is continued for 30 minutes, so that the aluminum nitride powder is evenly coated on the surface of the zinc oxide, and the amount of the silane coupling agent added is 1% of the mass of the mixed slurry. Finally, the slurry is filtered, dried and solidified, and after removing the solvent, the coated mixture is heat-treated. The heat treatment conditions are: carried out in an inert atmosphere (argon gas), the heat treatment temperature is 500°C, and the time is 40 minutes, so as to obtain modified zinc oxide.

[0078] In this embodiment, the silane coupling agent is KH550.

[0079] In this embodiment, the mass ratio of the red phosphorus in the halogen-free flame retardant to the halogen-free flame retardant FR-1 is 1:1.5.

[0080] In this embodiment, the anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1.3.

[0081] In this embodiment, the lubricant is molybdenum disulfide.

[0082] Another object of the embodiment of the present invention is to provide a method for preparing a high temperature resistant, breakdown resistant, flame retardant, reinforced PA material, comprising the following steps:

[0083] Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly;

[0084] The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 260°C.

[0085] Comparative Example 1.

[0086] The difference from Example 3 is that zinc oxide is used directly to replace the modified zinc oxide.

[0087] Comparative Example 2.

[0088] The difference from Example 3 is that no modified zinc oxide is added.

[0089] Comparative Example 3

[0090] The difference from Example 3 is that no red phosphorus is added to the halogen-free flame retardant.

[0091] Comparative Example 4.

[0092] The difference from Example 3 is that no halogen-free flame retardant is added.

[0093] Comparative Example 5.

[0094] The difference from Example 3 is that modified zinc oxide and halogen-free flame retardant are not added at the same time.

[0095] The products prepared in the above Examples 1-3 and Comparative Examples 1-5 were injection molded into test samples, and the test samples were tested for tensile strength (based on ASTM D638 standard test), aging resistance (based on ASTM G154-16 standard test, using QUV (340nm) accelerated aging tester, and the tensile strength retention rate was measured after 1000h), flame retardancy (based on UL94V standard test, the flame retardancy grade was obtained by test), and breakdown resistance (based on IEC 60243 standard test, the breakdown strength was obtained by test), and the results are shown in Table 1 below:

[0096] Table 1

[0097]

[0098] As can be seen from Table 1, compared with the products prepared in Examples 1-3 of the present invention and the products prepared in Comparative Examples 1-5, the PA materials prepared in the embodiments of the present invention have good comprehensive performance, and have good strength, flame retardancy, aging resistance and breakdown resistance. The data comparison between the comparative examples and the embodiments can further prove that the modified zinc oxide in the present invention can be used as an effective synergist in combination with red phosphorus and halogen-free flame retardant FR-1 to significantly improve the flame retardancy of the PA material, and the modified zinc oxide in the present invention can effectively improve the strength, breakdown resistance and aging resistance of the PA material.

[0099] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0100] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high temperature resistant, breakdown resistant, flame retardant and reinforced PA material, characterized in that: By weight, it includes the following raw materials: PA66 50-60 parts, glass fiber 25-35 parts, halogen-free flame retardant 10-18 parts, modified zinc oxide 0.5-2 parts, anti-aging agent 0.1-0.5 parts, lubricant 0.5-3 parts; Wherein, the halogen-free flame retardant is a mixture of red phosphorus and halogen-free flame retardant FR-1; The preparation method of the modified zinc oxide comprises the following steps: Add zinc oxide powder to a solvent, stir at a speed of 300-500 r / min for 10-40 min, stir evenly, and prepare a zinc oxide solution with a concentration of 3-10 wt%, wherein the solvent is one of ethanol and toluene; Aluminum nitride powder is added to a zinc oxide solution, and stirred at a speed of 450-650 r / min for 10-40 min, wherein the mass ratio of the aluminum nitride powder to the zinc oxide powder is 1:2-8, and then a silane coupling agent is added to the mixed slurry of aluminum nitride and zinc oxide, so that the temperature is maintained at 60-80°C, and the stirring is continued for 20-40 min, and the amount of the silane coupling agent added is 0.5-2% of the mass of the mixed slurry, and finally the slurry is filtered, dried and cured, and after removing the solvent, the coated mixture is heat-treated, and the heat treatment conditions are: in an inert atmosphere, the heat treatment temperature is 300-600°C, and the time is 30-50 min, so as to obtain modified zinc oxide; The particle size of the zinc oxide powder is 1-5 microns, and the particle size of the aluminum nitride powder is 20-50 nanometers.

2. The high temperature resistant and breakdown resistant flame retardant reinforced PA material according to claim 1, characterized in that: By weight, it includes the following raw materials: PA66 52 parts, glass fiber 28 parts, halogen-free flame retardant 12 parts, anti-aging agent 0.3 parts, modified zinc oxide 1.5 parts, lubricant 1.5 parts.

3. The high temperature resistant and breakdown resistant flame retardant reinforced PA material according to claim 1, characterized in that: The silane coupling agent is one of KH550, KH560 and KH570.

4. The high temperature resistant and breakdown resistant flame retardant reinforced PA material according to claim 1, characterized in that: The mass ratio of red phosphorus in the halogen-free flame retardant to the halogen-free flame retardant FR-1 is 1:1.5-2.

5. The high temperature resistant and breakdown resistant flame retardant reinforced PA material according to claim 3, characterized in that: The anti-aging agent is antioxidant 1010 and UV-1 in a mass ratio of 1:1-1.

5.

6. The high temperature resistant, breakdown resistant, flame retardant and reinforced PA material according to claim 1, characterized in that: The lubricant is molybdenum disulfide.

7. A method for preparing a high temperature resistant, breakdown resistant, flame retardant and reinforced PA material as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Weigh PA66, glass fiber, halogen-free flame retardant, anti-aging agent, modified zinc oxide and lubricant according to proportion, and mix the raw materials evenly; The uniformly mixed raw materials are input into a screw extruder, and the product is obtained after melt extrusion, granulation and drying, wherein the extrusion temperature is 220-260°C.